RAPID DETECTION OF WHITE SPOT SYNDROME VIRUS (WSSV) OF PENAEUS MONODON BY LATEX AGGLUTINATION TEST USING MONOCLONAL ANTIBODIES - Makesh, M.; Koteeswaran, A.; Chandran, N. Daniel Joy; Manohar, B. Murali; Ramasamy, V.; Chandramohan, A.; Raman, R. P.; Mukherjee, S. C. (Journal of Indian Fisheries Association, 2006)
Latex beads were sensitized with monoclonal antibodies (!\’lAb) raised against VP28 of WSSV. The optimum concentration of l\1Ab required to sensitize the latex beads was 125 J.Ig/ml. The sensitized latex beads ,were used to detect WSSV from PCR-positive stomach tissue homogenates obtained from infected shrimp. Stomach tissue homogenates from -infected shrimp agglutinated the sensitized latex beads within I 0 minutes, while uninfected samples did not produce any agglutination, although non-specific agglutinations were observed in some samples. The analytical sensitivity, analytical specificity, diagnostic sensitivity and diagnostic specificity of the (LAT) agglutination test were assessed. The analytical sensitivity of the test was 40 ng of purified WSSV (2 J.Iglml). The sensitized latex beads did not agglutinate with normal shrimp tissue or MBV-infected tissue homogenate. The test has a diagnostic sensitivity of 70 and 45o/o, respectively, compared to single-step and nested PCR. The diagnostic specificity of the test was 824%. This test is a simple and rapid on-farm test which can be used to corroborate clinical signs for the detection ofWSSVin grow-out ponds. Keywords: PenaerL-,’ monodon, white spot syndrome virus, monoclonal antibodies, latex agglutination test